Two new species of the genus Ectmetopterus (Hemiptera: Miridae: Orthotylinae) feeding on grass in India - Yeshwanth, H. M. (Zootaxa, 2015)
Two new species, Ectmetopterus mishmiensis sp. nov. from Arunachal Pradesh and E. nandiensis sp. nov. from Karnataka, India are described. Documentation is provided to substantiate that both new species feed on the grass Paspalum (Poaceae). The genus is recorded for the first time from India. Descriptions of the new species are provided, along with digital images of the genitalia, dorsal habitus, and images of live individuals on their host plant.